Antenatal Care (ANC) History Related To Chronic Energy Deficiency (CED) In Pregnant Women - Suja, Monica Dara Delia; Budiarti, Indah; Sulistianingrum, Lely (Tadulako University, 2025)
Introduction: Low body weight, decreased energy stores, and possibly impaired physical performance are all symptoms of chronic energy deficit (CED), a condition brought on by an prolonged absence of energy and protein intake. This kind of malnutrition can have serious health effects, particularly for teenagers and pregnant women. According to government regulations, pregnant women must have their pregnancy checked according to standards and routinely consume iron tablets. Aims: The purpose of this study was to identify the relationship between ANC history and iron tablet consumption level with the incidence of CED in pregnant women in the Way Kandis Public Health Center area in Bandar Lampung City. Methods: This study was conducted using a cross-sectional approach, with a total respondent of 48 pregnant women. Purposive sampling was used to choose participants, and in-person interviews were used to gather data. The statistical analysis used in this study was bivariate analysis using chi-square. Results: Antenatal care history and the incidence of CED was significantly related to the incidence of CED in pregnant women with p-value <0.05 and for the iron consumption was significantly related to the incidence of CED in pregnant women consumption and the incidence of CED with p-value <0.05 Conclusion: Adequate antenatal check-ups and regular consumption of iron tablets can prevent CED in pregnant women.